New Dicerurini from Europe, mostly Sweden (Diptera: Cecidomyiidae, Porricondylinae) - Jaschhof, Mathias; Jaschhof, Catrin (Zootaxa, 2019)
The taxonomy of several genera of the tribe Dicerurini (subfamily Porricondylinae) is revisited, induced by the discovery of 11 new species in Malaise catches of various provenances. The bulk of the specimens interpreted here is of Swedish origin. Species described as new to science are Desertepidosis grytsjoenensis sp. nov. (from Sweden), D. robusta sp. nov. (Sweden), Linnaeomyia pratensis sp. nov. (Czech Republic), Neurepidosis ekdalensis sp. nov. (Sweden), N. emarginata sp. nov. (Sweden, Czech Republic), N. hybrida sp. nov. (Sweden), Tetraneuromyia brevipalpis sp. nov. (Sweden, Slovak Republic), T. discrepans sp. nov. (Sweden), T. errata sp. nov. (Sweden), and T. lapponica sp. nov. (Sweden). A new genus, Gardenforsia gen. nov., is introduced for G. oelandica sp. nov. (Sweden), a new species with regressive male morphology. The generic definitions of Desertepidosis Mamaev & Soyunov, 1989 (including Ubinomyia Mamaev, 1990 syn. nov. as new junior synonym) and Linnaeomyia Jaschhof & Jaschhof, 2015 are revised. A key to males of Desertepidosis is presented. New information on the morphology and geographic distribution is provided for Linnaeomyia hortensis Jaschhof & Jaschhof, 2015; Tetraneuromyia bulbifera Mamaev, 1964; and T. lamellata Spungis, 1987.